2011
DOI: 10.1002/hed.21400
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of whole‐body PET and PET‐CT in initial M staging of head and neck cancer: A meta‐analysis

Abstract: Whole-body PET and PET-CT have good diagnostic performance in initial M staging of head and neck cancer; although PET-CT tends to have higher accuracy than PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
27

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 46 publications
0
21
0
27
Order By: Relevance
“…Cervical MRI remains the reference imaging for assessing mandibular invasion of tumor . Furthermore, FDG‐PET/CT offers in a whole‐body single scan a high diagnostic accuracy for M staging and synchronous disease . Moreover, Kyzas et al highlighted in their meta‐analysis the identical diagnostic performance of both techniques in detecting lymph node involvement .…”
Section: Discussionmentioning
confidence: 99%
“…Cervical MRI remains the reference imaging for assessing mandibular invasion of tumor . Furthermore, FDG‐PET/CT offers in a whole‐body single scan a high diagnostic accuracy for M staging and synchronous disease . Moreover, Kyzas et al highlighted in their meta‐analysis the identical diagnostic performance of both techniques in detecting lymph node involvement .…”
Section: Discussionmentioning
confidence: 99%
“…59 Table 3 summarizes available studies comparing the performances of different imaging approaches to detect distant metastasis of HNSCC. 52,53,[58][59][60][61][62][63] Globally, all these studies indicate that PET 6 CT is superior to conventional imaging. 18 F-FDG-PET shows higher accuracy (90-95%) than CT for the detection of distant metastasis.…”
Section: Lymph Node Involvement (Nodal Staging)mentioning
confidence: 93%
“…53 It is noteworthy that early detection of metastasis has a major impact on patient management avoiding unnecessary radical treatments. [54][55][56][57] Xu et al 58 conducted a meta-analysis evaluating the accuracy of PET and PET-CT in the initial M staging of HNSCC. This metaanalysis suggested that 209 (14.4%) of 1445 patients had distant metastasis or a second primary tumour (SPT).…”
Section: Lymph Node Involvement (Nodal Staging)mentioning
confidence: 99%
“…Head and neck cancer patients are at risk for developing distant metastasis and second primary tumors. PET-CT has been found to have ''good performance'' in M staging of head and neck cancer, and be more effective than CT of the chest and abdomen alone in detection of metastatic lesions [15]. We routinely perform PET scans with CECT, combining anatomic and functional evaluation into one setting.…”
Section: Cect Mri Ultrasound and Pet-ct Staging Of Op Primary Squammentioning
confidence: 99%